In silico studies of carotenoids from Chlorella sp. microalgae against s-shaped amyloid beta fibril - Zakaria, Norzalina; Hanifah, Nur Juliyana Bella; Azaman, Siti Nor Ani; Faujan, Nur Hana (Malaysian Institute of Chemistry, 2023)
Chlorella sp. is green freshwater microalgae have drawn great attention as a promising sustainable source of lipids and carotenoids. As neuroprotective natural products, carotenoids have shown promising preventive activity, as well as helping in slowing down Alzheimer's disease (AD) progression. However, the detailed information on the inhibition mechanism of amyloid beta (Aβ) fibril, one of the hallmarks of AD, by carotenoid compounds is poorly discussed in both experimental and computational studies. Thus, in this study, molecular docking simulations were performed to investigate the binding interactions between nine carotenoid compounds derived from Chlorella sp. against full sequence Aβ42 fibril. The results reveal that the binding energies ranged from -5.3 to -6.5 kcal/mol with binding interactions were dominated by hydrophobic interactions via π-alkyl, and only two carotenoid compounds, fucoxanthin and zeaxanthin, formed hydrogen bonds. In comparison, donepezil showed binding energy of -6.7 kcal/mol and interacted with Aβ42 residues through a hydrogen bond and hydrophobic interaction that involves alkyl, π- alkyl, π-sigma and π-π T-shape interactions. Our result showed that donepezil, fucoxanthin and zeaxanthin compounds disrupted the Aβ42 fibril by disaggregation pathway, which primarily interacted with residues within the hydrophobic (Phe19, Phe20, Val24, Ala30, and Ile32) and N-terminal (Tyr10, Val12, His13, and His14) regions. This study provides theoretical insights into the inhibitory mechanism of antioxidant compounds against Aβ fibril, which is beneficial for AD drug design.